KEARIFAN LOKAL WAYANG TOPENG MALANGAN - Balok Safarudin (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Malangan mask puppet has many plays containing local wisdom. One of itis existed in Adege Kadiri play and was shown in Gebyak Topeng SeninLegian show. This study focuses on how the form of local wisdoms in AdegeKadiri play are and have purpose to reveal the local wisdom in Adege Kadiriplay. This research uses analytical descriptive method. Then, the theory oflocal wisdom is used to analyze the local wisdom in Adege Kadiri play. Theconclusion of this research reveals that Adege Kadiri play contains localwisdom which can be used as guidance or teaching.